2012
DOI: 10.1136/sextrans-2012-050577
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted penile amoebiasis in Iran: a case series

Abstract: Clinicians need to be aware of cutaneous amoebiasis in sexually active men who practice unprotected insertive anal sex where intestinal amoebiasis is endemic. Wet mount microscopy is a rapid and useful diagnostic test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Penile amebiasis is a rare form of cutaneous amebiasis sexually transmitted through unprotected anal intercourse with a person suffering from intestinal amebiasis. It typically manifests as ulcers, which may be confused with squamous cell carcinoma of the penis . The first signs of penile cancer include change in color of the skin and skin thickening; the later symptoms are ulcers, discharge, and bleeding .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penile amebiasis is a rare form of cutaneous amebiasis sexually transmitted through unprotected anal intercourse with a person suffering from intestinal amebiasis. It typically manifests as ulcers, which may be confused with squamous cell carcinoma of the penis . The first signs of penile cancer include change in color of the skin and skin thickening; the later symptoms are ulcers, discharge, and bleeding .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there is not much clinical variability in penile amebiasis. Abdolrasouli et al . reported four young adults with sexually acquired penile amebiasis; one patient, who had a bisexual background and a history of sexually transmitted diseases, had developed bilateral inguinal lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the annual rate of anti- E. histolytica seropositivity in female outpatients was observed in a clinic for sexually transmitted diseases in Tokyo [ 17 ]. Furthermore, penile amebiasis was reported in men who practiced unprotected anal intercourse [ 18 ]. Results of the present study do not exclude a sexual transmission of E. histolytica .…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese study, researchers observed an increase in the annual rate of anti- E. histolytica seropositivity in female outpatients at a sexually transmitted disease clinic in Tokyo [ 17 ]. Penile amebiasis has been reported in men who practiced unprotected anal intercourse [ 18 ]. Very few studies about the link between infection with E. histolytica and sexual activity in women exist.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This form of intercourse among men is the cause of penile amoebiasis presenting as genital ulceration. 12 The first observation of EH in urine was made by Baelz in 1883, who found it in the blood-stained urine of a Japanese patient. 13 Subsequently, successive cases of urinary amoebiasis have been reported in the medical literature.…”
mentioning
confidence: 99%